But, excuse me, that is my book - Child, Lauren (New York : Dial Books for Young Readers, 2005)
When Lola's favorite book is not on the library's shelf, her older brother, Charlie, tries to find another book she will enjoy.
Text based on script written by Bridget Hurst and Carol Noble.
"Charlie & Lola"--T.p. verso.
A Junior Library Guild selection.
Keywords: Books and reading -- Fiction; Brothers and sisters -- Fiction; Libraries -- Fiction; Books and reading -- Juvenile fiction; Siblings -- Juvenile fiction; Libraries -- Juvenile fiction